The Influence of Capital Intensity Ratio and Profitability on Effective Tax Rate at PT Indocemen Tunggal Prakarsa Tbk - Wandira, Ayu; Huda, Nurul; Rahmatia (CV ODIS, 2024)
In Indonesia industry plays a very important role in economic development, with a large number of human resources, industry is able to absorb a wide range of workers so that it can add value to the output produced. Apart from the tax industry being one of the largest sources of state income, every industry is obliged to pay taxes effectively. This research aims to determine the effect of capital intensity ratio and profitability on the effective tax rate at PT Indocemen Tunggal Prakarsa Tbk. This form of research is associative research. The object of this research is a company operating in the raw goods sector, namely the company Indocemen Tunggal Prakarsa, Tbk. The sampling technique in this research uses purposive sampling. The data analysis technique used is quantitative methods with descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, correlation and coefficient of determination as well as hypothesis tests in the form of T tests and F tests. The test results show that the capital intensity ratio has a partial positive effect on the Effective Tax Rate. whereas. Profitability has a partial negative influence on the Effective Tax Rate